Highly sensitive contact pressure measurements using FBG patch in endotracheal tube cuff - Correia, R.; Blackman, O.R.; Hernandez, F.U.; Korposh, Sergiy; Morgan, S.P.; Hayes-Gill, B.; James, S.W.; Evans, D.; Norris, A. (2016)
A method for measuring the contact pressure between an endotracheal tube cuff and the trachea was designed and developed by using a fibre Bragg grating (FBG) based optical fibre sensor. The FBG sensor is encased in an epoxy based UV-cured cuboid patch and transduces the transversely loaded pressure into an axial strain that induces wavelength shift of the Bragg reflection. The polymer patch was created by using a PTFE based mould and increases tensile strength and sensitivity of the bare fibre FBG to pressure to 2.10×10-2 nm/kPa. The characteristics of the FBG patch allow for continuous measurement of contact pressure. The measurement of contact pressure was demonstrated by the use of a 3D printed model of a human trachea. The influence of temperature on the measurements is reduced significantly by the use of a second FBG sensor patch that is not in contact with the trachea. Intracuff pressure measurements performed using a commercial manometer agreed well with the FBG contact pressure measurements. © (2016) COPYRIGHT Society of Photo-Optical Instrumentation Engineers (SPIE). Downloading of the abstract is permitted for personal use only.